STEREOSELECTIVE OXIDATIVE COUPLING OF METHYL TRANS-FERULATE TO (±)-TRANS-DEHYDRODIFERULATE DIMETHYL ESTER BY Trametes versicolor FC: AN ENANTIOSELECTIVE GREEN APPROACH - Eliane O. Silva; Herbert J. Dias; Anderson R. M. Oliveira; Antônio E. M. Crotti (Química Nova)
Chemoenzymatic strategies to synthesize complex molecules have been developed by combining biocatalytic and synthetic methods in a multistep approach toward a target molecule. Dihydrobenzofuran neolignans (DBNs), a class of plant-derived natural compounds, display several biological activities. Oxidative coupling of phenylpropanoids is commonly used to obtain DBNs, but yields are low, and stereochemical control is poor. This study reports the novel eco-friendly and stereoselective conversion of methyl trans-ferulate (1) into DBN 2 ((±)-trans-dehydrodiferulate dimethyl ester) promoted by Trametes versicolor FC in 47% yield. Compared to Ag2O-promoted oxidative coupling, this biotransformation approach is enantioselective (66.7% ee of the main enantiomer) and affords DBN 2, as confirmed by chiral-HPLC (high-performance liquid chromatography) and NMR (nuclear magnetic resonance) data analyses. Our preliminary results highlighted the combination of biotransformation and traditional chemical processes as a promising starting point for obtaining DBNs from the corresponding phenylpropanoids enantioselectively.